Sporothrix schenckii Cell Wall Peptidorhamnomannans - Bezerra, Leila L. (Frontiers in Microbiology, 2011)
This mini-review article is dedicated to clarifying certain important biochemical aspects of S. schenckii cell wall peptidorhamnomannans. Cell wall components involved in the host interaction such as antigens as well as a gp70 adhesin are important molecules present on the surface of the yeast parasitic phase. Other structural glycoconjugates present on the fungus cell surface will also be described here. Knowledge of the fine structure of carbohydrate epitopes expressed on the surface in both morphological phases of S. schenckii permitted the development of noninvasive immunochemical methods to diagnose human and feline sporotrichosis.